Effect of high intensity ultrasound on gelation properties of silver carp surimi with different salt contents - Gao, Xia (Ultrason Sonochem, 2020)
Surimi from silver carp with different salt contents (0–5%) was obtained treated by high intensity ultrasound (HIU, 100 kHz 91 W·cm(−2)). The gelation properties of samples were evaluated by puncture properties, microstructures, water-holding capacity, dynamic rheological properties and intermolecular interactions. As the salt content increased from 0 to 5%, gel properties of surimi without HIU significantly improved. For samples with low-salt (0–2% NaCl) content, HIU induced obvious enhancement in breaking force and deformation. HIU promoted the protein aggregation linked by S—S bonds, hydrophobic interactions and non-disulfide covalent bonds in surimi gels with low-salt content. Moreover, microstructures of HIU surimi gels with low-salt content were more compact than those of the corresponding control samples. HIU also improved the gelation properties of surimi with 3% NaCl to an extent. However, for high-salt (4–5% NaCl) samples, HIU decreased the breaking force and deformation of surimi gels due to the degradation of proteins suggested by increased TCA-soluble peptides. In conclusion, HIU effectively improved the gelation properties of surimi with low-salt content (0–2% NaCl), but was harmful for high-salt (4–5% NaCl) surimi. This might provide the theoretical basis for the production of low-salt surimi gels.